Just another teen movie: analyzing portrayals of teenage romantic relationships across a decade of top-grossing teen films - Zwier, Abigail J., author; Griffin, Cindy L., advisor; Lupo, Jonathan, committee member; Coke, Pamela, committee member (Colorado State University. Libraries, 2012)
America's teenagers exhibit dating attitudes and behaviors that have been labeled both risky and harmful. This critical film study examines the implicit and explicit messages present in teenage films' portrayal of teenage romantic relationships so as to better understand the possible influences of the messages present in these films as teens seek them out for information and advice about romantic relationships in high school. I uncover the themes running throughout the top grossing U.S. box office feature films for each year over the course of a decade (2000-2010) that depict teenage romantic relationships in high school settings. The study is a critical film analysis in which focuses on answering two main questions: (1) what is being communicated about teenage romantic relationships in these films? and (2) how are those messages being communicated? To answer the questions I look at the dating scripts that each of the main teenage romantic relationships follow and find that two main narrative structure undergird all of the films: narratives of pursuit and rescue. Then, I consider the agency that each of the characters in the main romantic relationship exhibit, finding that male characters are featured with active agency and female characters with very little agency. Finally, I look at the hidden ideologies present within the films and uncover a patriarchal agenda, which follows the same, unoriginal scripts present in a lot of romance films. Ultimately, I conclude that these films give the allusion of progressive agendas but underneath the mask are simply the same traditional plots we have been seeing in films for decades.
Keywords: teen; communication; film; gender; relationships; romance